Toxicity of contaminated soils with heavy oil on seedlings of moriche palm Mauritia flexuosa L. f. (Bioagro, 2020)
An acute test of toxicity was performed with seedlings Mauritia flexuosa exposed to  contaminated  soils in concentrations of 0, 4, 8, 16, 32 y 64 % of heavy crude oil under greenhouse conditions. Concentrations of up to 16 % did not significantly affect the survival of seedlings, while at the maximum concentration of 64 % did not survive any seedling. In correlation with survival, stem biomass and total biomass did not decreased until a concentration of heavy oil of 16 %, while root biomass and shoot/root ratio showed no differences between concentrations where seedlings survived. The results show a high tolerance M. flexuosa to soil contamination with heavy crude oil and its potential to reforest contaminated soils with such type of hydrocarbon.
Keywords: Biomass; heavy crude oil; reforestation; seedling survival; soil pollution